Al-Si Alloys Casts by Die Casting A Case Study - Ružbarský, Juraj (SpringerBriefs in Applied Sciences and Technology,, 2019)
This book presents a study on the influence of selected technological parameters of die casting upon strength and use properties of Al-Si alloy casts produced in die casting. It contains a theoretical part describing the principles of casting technology, and its practical part revolves around the relationship between selected technological parameters of die casting in regard to strength and use properties represented by tensile strength and porosity of die casts. .